PENGARUH KEAKTIFAN KOMITE AUDIT DAN AUDIT EKSTERNAL TERHADAP MANAJEMEN LABA - Nonie Dewinta; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2015)
Audit committee and external audit have a very important role to oversee the financial reporting process and monitor the propensity of a company managers to manipulate earnings. Monitoring mechanism is a key factor to reduce conflicts of interest and any opportunistic behavior from the manager. This study aims to examine the effect of activeness of the audit committee, external audit and the interaction between activeness of the audit committee and external audit on earnings management in the non-financial companies in Indonesia. This study uses secondary data from annual reports and financial statements on non-financial companies listed on the Indonesia Stock Exchange in 2013. The sampling method used is purposive sampling. The total number of samples in this study were 178 data. Variable earnings management, activeness of the audit committee, external audit and the interaction between activeness of the audit committee and external audit analyzed by Ordinary Least Square regression. The results of this study indicate that the activeness of the audit committee  and  external audit  Big 4  are  significantly negative effect  on earnings management. However, the interaction between activeness of the audit committee and external audit significantly positive effect on earnings management. This finding suggests that both the monitoring mechanisms functioning jointly within the firm would indicate potential increasing earnings management.